A study of inoculation route and dosage levels on embryonated chicken eggs as media for testing tea mistlestoe (Scurrula oortiana) extract activity - Sri Murtini; R Murwarni; F Satrija; M.B.M Malole (Indonesian Center for Animal Research and Development (ICARD), 2006)
Tea mistlestoe extract (Scurrula oortiana) has cytotoxic activity which is potential to be used in preventing viral induced-chicken tumor. The following study was designed to evaluate the effects of different inoculation routes, dosage levels, and strains of embryonated chicken eggs as media for testing the tea mistlestoe extract (Scurrula oortiana) antiviral activity. Proper inoculation route was examined by inoculation of the extract at dose level of 0,2 mg/egg into embryonated layer eggs via allantoic cavity, chorio-allantoic membrane, and yolk sac. Effect of dose level of tea mistlestoe extract on embryo development was examined in groups of embryonated broiler eggs inoculated with the extract at 0.02, 0.2, 2, 20, or 200 mg/egg. Inoculation of tea mistlestoe extract into allantoic cavity was the safest procedure as indicated by the absence of embryos mortality, and faster embryo growth compared to those of chorio-allantoic membrane and yolk sac-inoculated eggs. The extract induced different growth effects when inoculated into embryonated layer or broiler eggs. Administration of the extract at dose levels between 0,02–200 mg/egg reduced significantly the weight of broiler embryoes, but not the relative weights of liver, heart and spleen. Administration of similar dosage in layer embryoes did not cause any significant difference in the embryoes weight. This study suggests that the study of antiviral activity of tea mistlestoe extract in embryonated chicken eggs should be carried out on embryonated eggs of layer breeds and the extract should be inoculated via allantoic cavity. Key Words: Scurrula oortiana, Embryonated Chicken Eggs, Enti Viral Activity